Gender similarities and differences in the perception of caring among nurses during the COVID-19 pandemic: a mixed-methods study - Lai Kun Tong; Ming Xia Zhu; Si Chen Wang; Pak Leng Cheong; Iat Kio Van (BMC, 2023)
Abstract Background Caring is the essence and core of nursing. Current studies on the effect of gender on nurses' perception of caring have been inconsistent. Most of these studies were quantitative and conducted before the COVID-19 pandemic. The study aimed to explore the gender similarities and differences in nurses' perception of caring during the COVID-19 pandemic. Methods In 2020, a cross-sectional mixed-method study was conducted in 11 cities in China using structured online questionnaire (n = 8030) and face-to-face individual interview (n = 42). Data collection tools included the Caring Dimensions Inventory and semi-structured interview. Results In stepwise multivariable linear regression analysis, female nurses scored 1.93 points higher on caring than male nurses, after completely controlling for the other factors. The interview results showed that both male and female nurses agreed that caring was to deal with three kinds of relationships, namely nurses and people, nurses and themselves, nurses and society. There were gender differences in the connotation of caring between nurses and themselves, but not in the connotations of caring between other relationships. The ranking of the importance of caring connotations among these relationships showed no gender difference except between nurses and themselves. Conclusion The quantitative findings suggest that gender influences nurses' perception of caring. The qualitative findings demonstrate that nurses regard themselves as both recipients and implementers of caring. The qualitative results indicate nurses of different genders have similarities and differences in their perception of caring, and the biggest difference lies in the relationship between nurses and themselves.